Influence of Ni interlayer on interfacial microstructure and mechanical properties of Ti-6Al-4V/AZ91D bimetals fabricated by a solid–liquid compound casting process - Fulin Wen (Journal of Magnesium and Alloys, 2021)
The solid–liquid compound casting of Mg-AZ91D and Ti-TC4 alloys was developed by using pure Ni electro-deposited coating. The pouring temperatures of 660 ℃, 690 ℃, 720 ℃ and 750 ℃ were chosen to investigated the effects of casting temperatures on microstructural evolution, properties, and fracture behaviors of Ni-coated TC4/AZ91D bimetals by the solid–liquid compound casting (SLCC). The scanning electron microscopy (SEM) and the energy dispersive spectroscopy (EDS) results showed that the interfacial zone mainly composed of nickel, Mg2Ni and Mg-Al-Ni in the bimetals cast at 660 ℃. As the pouring temperature was increased to 750 ℃, the width of the interface zone, which mainly composed of δ(Mg), Mg2Ni, Mg-Al-Ni, Mg3TiNi2 and Al3Ni, gradually increased. The microhardness tests showed that the micro-hardness of the interface zone was smaller than that of TC4 substrate but larger than that of the cast AZ91D matrix. At the pouring temperature of 720 ℃, the Ni-coated TC4/AZ91D bimetals had the most typical homogeneous interface, which had granular Mg-Al-Ni ternary phase but no ribbon-like Al3Ni binary phase, and achieved the highest shear strength of 97.35 MPa. Meanwhile, further fracture behavior analysis showed that most fracture failure of Ni-coated TC4/AZ91D bimetals occurred at the Mg2Ni + δ(Mg) eutectic structure and Al3Ni hard intermetallic.